AUDIT BERBASIS BIG DATA DALAM SEKTOR ASURANSI DI INDONESIA: KAJIAN LITERATUR TERHADAP TANTANGAN DAN STARTEGI IMPLEMENTASI - Rahmah, Rizky Aulia (Politeknik Keuangan Negara STAN, 2025)
Research objective: This study aims to examine the implementation of big data-based audit in the Indonesian insurance sector, focusing on challenges and strategies. Method: A systematic literature review was conducted by collecting and qualitatively analyzing publications from international and national journals during 2014–2024. Research findings: The implementation of big data audit in Indonesia is constrained by technological infrastructure, auditor competency, data quality, and inadequate regulation. Strategies such as training, IT system enhancement, and regulatory development are proposed as solutions. Practical implication: This study provides guidance for stakeholders to accelerate digital audit transformation in the insurance sector.